Attention Deficit Hyperactivity Disorder in Preschool Children: A Cross-Sectional Study of Clinical Profile and Co-morbidity. Issue 3 (May 2023) - Addanki, Sai Sandhya; Chandrasekaran, Venkatesh; Kandasamy, Preeti
Background: Diagnosis of Attention Deficit Hyperactivity Disorder (ADHD) in preschool children is challenging and complicated owing to the presence of developmentally appropriate overactivity and a dynamic developmental/learning phase shaping their behaviour. We aimed to study the clinical profile and co-morbidity of ADHD in preschool children. Methods: Fifty consecutively presenting preschool children with ADHD were enrolled from our child guidance clinic (CGC) between January 2017 and December 2018. The diagnosis and assessment of comorbidities were based on the DSM-5 criteria and Vanderbilt teacher and parent rating scales. Relevant clinical and sociodemographic profiles were assessed and analyzed for association with ADHD subtypes and comorbidity. Results: Preschool children with ADHD constituted 8% of all patients visiting the CGC and one-fifth of all children with ADHD. Male:female ratio was 11.5:1. Hyperactive-impulsive was the commonest type, and oppositional defiant disorder (ODD) was the commonest comorbidity. Most children belonged to the lower-middle socioeconomic group. Language delay was observed in 20%. Median social quotient measured using the Vineland Social Maturity Scale was 83. Conclusions: Preschool children predominantly have the hyperactive impulsive type of ADHD. Isolated language delay was the predominant comorbid developmental disorder, and ODD was the predominant comorbid behavioural disorder. Addressing these issues would help in the appropriate management of these children.